Enhanced photocatalytic activity of Ce-doped ZnO nanopowders synthesized by combustion method - Ahmad, M.; Ahmed, E.; Zafar, Fezza; Khalid, N.R.; Niaz, N.A.; Hafeez, Abdul; Ikram, M.; Khan, M. Ajmal; HONG, Zhanglian (Journal of rare earths, 2015)
Facile and fast combustion method was used to synthesize Zn O and Ce-doped Zn O（CZO） nanocrystalline powders photocatalysts with different cerium concentrations（0.5 wt.%–10.0 wt.%） followed by calcination at 700 oC for 3 h. The prepared samples were characterized by a variety of characterization techniques such as X-ray diffraction（XRD）, scanning electron microscopy（SEM） combined with energy dispersive X-ray diffraction（EDX）, transmission electron microscopy（TEM）, UV-visible spectroscopy, BET surface area analyser and photoluminescence spectroscopy（PL）, to study the crystal structure, surface morphology, chemical composition and optical properties. It was observed from XRD results that synthesized powders had hexagonal wurtzite structure with the smallest crystallite size about 13 nm. Absorption spectra showed that cerium doping enhanced the light absorption properties towards the visible light region. Photoluminescence spectra for Ce-doped Zn O samples exhibited relatively weak near band edge（NBE） emission peaks as compared to that of pristine Zn O. The photocatalytic activities of the prepared samples were evaluated by photocatalytic degradation of Rhodamine B（Rh B） under UV light and visible light（λ≥420 nm） irradiation. The textile mill effluent containing organic matters was also treated under sunlight using photocatalysis and the reduction in the chemical oxygen demand（COD） of the treated effluent revealed a complete destruction of the organic molecules along with colour removal. The results showed that the CZO photocatalyst doped with 3.0 wt.% cerium exhibited four times enhanced photocatalytic activity compared to pure Zn O. The enhanced photocatalytic activity could be attributed to extended visible light absorption and inhibition of the electron-hole pair＇s recombination.